The Academic Identity Development of International Doctoral Students: An Exploration from a Sociocultural Perspective - Phan, Anh (Journal of International Students, 2022)
This qualitative study examines the factors that facilitate or inhibit the academic identity development of four Vietnamese doctoral students in Denmark. Using the combination of Genetic method and Activity theory, the paper provides insights into the participants’ experiences of becoming and being an academic, which is context-dependent and personal. The findings suggest that the sense of being academics was strengthened when doctoral students were empowered by their supervisors, and other members of the academic community validated their membership. The students also enacted their agency to move beyond the student role and establish a confirmed academic identity, though there were situations when their agency did not lead to desirable outcomes. The study is one among a few that incorporated the personal life history of doctoral students to examine their academic identity development, arguing for its inclusion to have a comprehensive picture of students’ learning and the process of becoming an academic.